Experimental Investigation of Continuous Fluidized Bed Spray Granulation with Internal Classification. (2015) - Schmidt, Martin; Hoffmann, Torsten; Bück, Andreas; Tsotsas, Evangelos
Abstract: Free flowing and dust free granules with defined properties can be produced from solid-containing liquids like suspensions, solutions or melts by means of fluidized bed spray granulation. In the presented work, granules are produced from a 30 w-% solution of sodium benzoate by layering. The granules are discharged through a classifying tube installed centrally in the distributor plate of the fluidized bed. New nuclei for the granulation are produced solely internally through overspray. The presented experiments investigate the influence of the classifying, drying and fluidizing parameters on nucleation, product properties and process stability.